Responsive Interfacial Assemblies Based on Charge‐Transfer Interactions. (10th November 2021) - Sun, Shuyi; Xie, Chenxia; Chen, Jie; Yang, Yang; Li, Hui; Russell, Thomas P.; Shi, Shaowei
Abstract: Charge transfer (CT) interactions have been widely used to construct supramolecular systems, such as functional nanostructures and gels. However, to date, there is no report on the generation of CT complexes at the liquid–liquid interface. Here, by using an electron‐deficient acceptor dissolved in water and an electron‐rich donor dissolved in oil, we present the in situ formation and assembly of CT complex surfactants (CTCSs) at the oil–water interface. With time, CTCSs can assemble into higher‐order nanofilms with exceptional mechanical properties, allowing the stabilization of liquids and offering the possibility to structure liquids into nonequilibrium shapes. Moreover, due to the redox‐responsiveness of the electron‐deficient acceptor, the association and dissociation of CTCSs can be reversibly manipulated in a redox process, leading to the switchable assembly and disassembly of the resultant constructs. Abstract : By taking advantage of charge transfer (CT) interactions between water‐soluble electron‐deficient acceptor and oil‐soluble electron‐rich donor, the formation and assembly of CT complex surfactants (CTCSs) at the oil–water interface is presented. With CTCSs as the building block, higher‐order nanofilms with exceptional mechanical properties are produced, which can be used to stabilize and structure liquids.